Phytochemical studies on Alstonia scholaris leaves - Ragasa, Jose Y.; Santos, Rizalina B. (Quezon City: Department of Pharmaceutical Chemistry, College of Pharmacy, University of the Philippines, 1984.)
The alkaloid content of Dita (Alstonia scholaris R. Br.) leaves was isolated. Extraction of the alkaloids was done with the use of methanol containing one percent of hydrochloric acid in a percolator. The methanolic extract was evaporated under reduced pressure. The concentrated extract was taken up with water and treated with supercel. Then it was filtered and the precipitate was washed with water. Chloroform was added. The mixture was treated with ammonium hydroxide drop by drop until alkaline pH was reached. The chloroform layer was collected and acidified with 1 percent HCl. The combined extract was dehydrated with anhydrous sodium sulfate and concentrated in a water bath. Thin layer chromatography was performed to separate specific alkaloids and then the purified alkaloids collected and subjected to ultra violet analysis and UV.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, November 1984.
Keywords: Alstonia; Dita